Pendampingan Edukasi Anti Bullying dan Kekerasan Seksual bagi Siswa Sekolah Menengah Kejuruan Negeri 14 Medan - Syahrial Arif Hutagalung; Dita Kartika Sari Hasibuan; Khairi Anshori; Lia Hartika; Nasruddin (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
School-based violence, including bullying and sexual violence, remains a critical issue within educational settings. Students’ limited understanding of its forms and impacts, coupled with a deeply rooted culture of silence, often causes cases of violence to remain undetected. This community service program aimed to enhance the literacy of students at SMK Negeri 14 Medan regarding bullying and sexual violence through an educational, interactive, and collaborative approach involving lecturers, students, and teachers. The program employed a Participatory Action Research (PAR) approach and was implemented in three stages: preparation, implementation, and evaluation. Evaluation was conducted through pre-test and post-test assessments to measure changes in students’ understanding. The results indicated a significant improvement in students’ literacy, as reflected in the increase in average scores from the pre-test to the post-test, accompanied by greater willingness among students to report incidents and strengthened teacher capacity in fostering a safe and supportive school environment. These findings demonstrate that the PAR-based educational intervention effectively improved students’ awareness and contributed to the development of a more protective school culture.